The Conflict Of Interest About Gender Paradigm In West Sumatera - Reza Fahmi (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2015)
The Minangs are the world's largest matrilineal society; properties such as land and houses are inherited through female lineage. Some scholars argue that this might have caused the diaspora(Minangkabau,